Wood lignocellulosic stabilizers: effect of their characteristics on stability and rheological properties of emulsions - Ho, Thao Minh; Abik, Felix; Hietala, Sami; Isaza Ferro, Estefania; Pitkänen, Leena; Juhl, Dennis W.; Vosegaard, Thomas; Kilpeläinen, Petri O.; Mikkonen, Kirsi S. (Springer Science and Business Media LLC, 2022)
Lignocellulosic materials from the forest industry have shown potential to be used as sustainable hydrocolloids to stabilize emulsions for many applications in life science and chemical industries. However, the effect of wood species and recovery method on the product’s properties and ability to stabilize emulsions of isolated lignocellulosic compounds is not well understood. Hemicelluloses, abundant lignocellulosic side stream, exhibit differences in their water solubility, anionic character, lignin content, and degree of acetylation. Here, we explored stability and rheological properties of model emulsions (5% hexadecane and 1% stabilizer, w/w) stabilized by different grades of sprucewood galactoglucomannan (GGM) and birchwood glucuronoxylan (GX) hemicelluloses. The results were compared to known soluble, insoluble, charged, and non-charged cellulosic stabilizers, namely methyl cellulose (MC), carboxymethyl cellulose (CMC), anionic- and nonionic-cellulose nanocrystals (aCNC and dCNC). The results showed that GX emulsions were highly stable compared to GGM emulsions, and that deacetylation and lignin removal markedly reduced emulsion stability of GGM. Carboxymethylation to increase anionic characters enhanced the emulsion stabilization capacity of GGM, but not that of GX. Investigating flow behaviors of emulsions indicated that hemicelluloses primarily stabilize emulsions by adsorption of insoluble particles, as their flow behaviors were similar to those of cellulose nanocrystals rather than those of soluble celluloses. Understanding the impact of the variations in composition and properties of hemicellulose stabilizers to stabilize emulsions allows tailoring of their recovery processes to obtain desirable hydrocolloids for different applications.
Keywords: hemicellulose; cellulose; lignin; galactoglucomannans; xylans; spruce